2010
DOI: 10.1158/1055-9965.epi-10-0066
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Operation of a Biorepository for Molecular Epidemiologic Studies in Costa Rica

Abstract: Background: The Proyecto Epidemiológico Guanacaste (PEG) has conducted several large studies related to human papillomavirus (HPV) and cervical cancer in Guanacaste, Costa Rica in a long-standing collaboration with the U.S. National Cancer Institute. To improve molecular epidemiology efforts and save costs, we have gradually transferred technology to Costa Rica, culminating in state-of-the-art laboratories and a biorepository to support a phase III clinical trial investigating the efficacy of HPV 16/18 vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In addition, an observational study in Guanacaste, Costa Rica will provide a six-year follow-up of women who received the bivalent vaccine in the Costa Rican Vaccine Trial and unvaccinated women. 37 In the meantime, the head-to-head study of the two vaccines has provided compelling evidence that the bivalent vaccine induces a stronger immune response than the quadrivalent vaccine, with higher levels of neutralizing antibodies (which likely mediate protection offered by prophylactic vaccines) maintained at two years post-vaccination. 43,44 A study of the bivalent vaccine has shown that levels of neutralizing antibodies against both HPV-16 and HPV-18 remain several-folds above natural infection levels up to 8.4 years after vaccination.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In addition, an observational study in Guanacaste, Costa Rica will provide a six-year follow-up of women who received the bivalent vaccine in the Costa Rican Vaccine Trial and unvaccinated women. 37 In the meantime, the head-to-head study of the two vaccines has provided compelling evidence that the bivalent vaccine induces a stronger immune response than the quadrivalent vaccine, with higher levels of neutralizing antibodies (which likely mediate protection offered by prophylactic vaccines) maintained at two years post-vaccination. 43,44 A study of the bivalent vaccine has shown that levels of neutralizing antibodies against both HPV-16 and HPV-18 remain several-folds above natural infection levels up to 8.4 years after vaccination.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…[14][15][16][17] Moreover, the major population of Costa Rica, that of its Central Valley, has been the subject of genetic scientific interest [18][19][20][21][22][23][24][25][26] due to its interesting demographic history including claims for relative isolation, 27,28 while that of its northwestern province of Guanacaste has been a hub for largescale human papilloma virus vaccine testing clinical trials. [29][30][31][32][33] All these characteristics make the study of HLA allele and haplotype frequencies in these countries of special interest.…”
mentioning
confidence: 99%
“…The staff at each clinic includes a clinician, an interviewer, a field work supervisor, a driver and a janitor. The headquarters in Liberia coordinates appointments using a data-management system developed for CVT and modified for LTFU; the headquarters also houses the fully equipped biospecimen repository (24), document center, and teams of study physicians, data entry, information technology and quality control, as well as processing laboratories for cervical sample aliquotting, cytology slide production, blood processing, cryopreservation, histology, and HPV testing by hybrid capture 2 (HC2). Participant records and specimens are centralized at the Liberia headquarters and transported daily to and from the clinics in study vehicles.…”
Section: Methodsmentioning
confidence: 99%